Martin Heideggers Festrede "Gelassenheit": die Frage nach dem Wesen der Technik und dem Denken des Menschen - Denker, Alfred (Ekstasis: Revista de Hermenêutica e Fenomenologia, 2020)
The main objective of this article is to elucidate, from the discourse Gelassenheit, which occurred in 1955, problems that pervade Martin Heidegger’s late philosophy, especially with regard to the issue of technique and human thought. To problematize the technique implies establishing the distinction between meditative thinking and calculating thinking, in addition to calling into question the position of the human being in the totality proper to the entity. The technique would therefore be a way of claiming the individual and a transformation of his essence, as well as one of the faces of the consummation of nihilism present in the current era. Palavras-chave: Serenidade. Técnica. Heidegger. Pensamento histórico do ser.